Unveiling gender dysphoria experiences in Turkish young adults: Challenges, perspectives, and implications in health care settings - YORGUNER, NEŞE (My University, 2023)
Purpose: Gender dysphoria (GD) emerged as a focal area in child and adolescent development research. While the intricacies of diagnosis and interventions for GD intertwine with diverse socio-cultural challenges, a notable dearth of knowledge exists about the experiences of transgender (TG) individuals during their formative years in Turkey. This study aims to unveil these experiences, shedding light on the challenges, perspectives, and implications in health care settings. Patients and Methods: Our study encompassed 125 participants: 62 TGs under clinical follow-up, and a control group of 63 cisgender individuals. Surveys tailored to TG participants addressed early GD experiences, gender-typed activity participation, and psychosocial challenges from childhood through adolescence. Additionally, both cohorts contributed to a survey on attitudes towards community-based interventions, allowing for a comparative analysis of their perspectives. Results: TGs identified their GD around age 10.77. Female-to-male TGs showed more involvement in traditionally male-associated activities, whereas male-to-female engaged more in female-associated domestic role-plays (p<0.001). Over a third (37.09%) faced ostracization or bullying due to GD, 45.16% encountered verbal abuse, and 12.90% reported physical violence. Additionally, 40.32% had undergone treatment for depression and anxiety disorders. Most participants supported awareness initiatives, advocating for open gender expression, and normalizing the experiences of TG youth. Furthermore, 88.71% of TGs emphasized the importance of enhancing the expertise of professional groups, such as medical and mental health practitioners, in GD matters, a sentiment echoed by 68.25% of cisgender participants (p=0.030). While medical interventions were the least favored strategy at 32.80% overall, 46.78% of TGs supported it, compared to 19.05% of controls (p=0.010). Conclusion: Our study underscores the challenges faced by TG individuals during development. Early recognition, societal awareness, enhanced training in professional healthcare environments, and comprehensive support are crucial for fostering acceptance and reducing adversity among children and adolescents navigating GD.
Keywords: Sosyal ve Beşeri Bilimler; Psikoloji; Sağlık Bilimleri; Social Sciences and Humanities; Psychology; Health Sciences; Klinik Tıp (MED); Temel Bilimler (SCI); Psikiyatri; Clinical Medicine (MED); Natural Sciences (SCI); PSYCHIATRY; PSYCHOLOGY; Genel Psikoloji; Sosyal Bilimler ve Beşeri Bilimler; Psikiyatri ve Ruh Sağlığı; General Psychology; Social Sciences & Humanities; Psychiatry and Mental Health; childhood play behaviors; early interventions; gender dysphoria; health care; mental health; psychosocial challenges